2015
DOI: 10.7314/apjcp.2015.16.7.2653
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Carcinoma Incidence in North Tunisia: Negative Trends in Adults but not Adolescents, 1994-2006

Abstract: Nasopharyngeal carcinoma (NPC) is the second most common neoplasm of head and neck in Tunisia. The distribution is bimodal with a first period occurrence between 15 and 20 years old and a second peak at around 50 years of age. Undifferentiated carcinoma of nasopharynx type III (UCNT) is the predominant histological type (93.4%). Data of cancer registry of North Tunisia confirmed that it is an intermediate risk area for NPC with overall ASRs of 3.6 and 1.6/100,000 respectively in males and females. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
1
14
0
4
Order By: Relevance
“…EBV, in interaction with salted fish and preserved food consumption, which are high in nitrous compounds and volatile nitrosamines, induces carcinogenic development for NKC, the predominant histology in endemic areas . In several high risk areas, a noticeable decline in NPC incidence has been reported . Our study showed a significant decreasing NPC mortality in Hong Kong.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…EBV, in interaction with salted fish and preserved food consumption, which are high in nitrous compounds and volatile nitrosamines, induces carcinogenic development for NKC, the predominant histology in endemic areas . In several high risk areas, a noticeable decline in NPC incidence has been reported . Our study showed a significant decreasing NPC mortality in Hong Kong.…”
Section: Discussionsupporting
confidence: 48%
“…There were about 85,000 incident cases and over 50,000 deaths from nasopharyngeal carcinoma (NPC) worldwide in 2012 . The global distribution of incidence and mortality showed a unique disparity, with extremely high rates (over 20–30/100,000 men and 10/100,000 women) in some regions of Southern China, Hong Kong, Taiwan, Singapore, other areas of Southeast Asia, selected Chinese migrants (mostly to North America), and in North Africa . In non‐endemic areas including most western countries, Latin America and Japan, NPC is a rare malignancy with incidence rates lower than 1/100,000 …”
mentioning
confidence: 99%
“…In the younger age group, the rates were stable. (Wided et al, 2015) Importantly, along with the declining incidence of NPC, the mortality rate has also declined. (Huang et al, 2012) The declining rates observed in our studies, consistent with what have been generally reported elsewhere are accounted for by several important factors.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with have been reported in other countries. (Wided et al, 2015) In Singapore, undifferentiated NPC accounts for 85.1% of all nasopharyngeal cancers. (Singapore Cancer Registry 2007) Of the three tumor types, undifferentiated NPC has been strongly linked to EBV infection (Raab-Traub.…”
Section: Discussionmentioning
confidence: 99%
“…The geographical distribution of NPC incidence is rather distinct and well-defined all over the world (2). Although it rarely occurs in most areas of the world, NPC is among the most common cancers in Southeast Asia and China (3,4).…”
Section: Introductionmentioning
confidence: 99%